Comparative Performance of Hay Densification Machines - Sahay, Chandra Shekhar; Pathak, Prabha Kant (Journal of Agricultural Engineering, 2013)
Densification and baling of hay material is required to reduce its volume for easy transport. Three types of densification machines viz. i) stationary baler; ii) movable baler; and iii) field baler were evaluated for densification of different hay materials. The output from stationary, movable and field baler were 0.045, 0.21 and 0.86 t.h-1, respectively. Densification with stationary baler needed all the hay material to be carried to the densification yard, thus increasing man power requirement and costs while movable baler could be moved to the place of availability of raw material. Field baler could collect and bale the harvested hay material spread on field. Field baler also operated under stationary condition with manual feeding of hay material heaped at one place. The cost of operation with stationary, movable and field baler were Rs.14400, 4700 and 1500 Rs.t-1 of bales formed, respectively. Â